UPAYA PENEGAKAN HUKUM DALAM MEMINIMALISIR TINDAK PIDANA PEMALSUAN SURAT IZIN MENGEMUDI DI KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Counterfeiting is essentially to make an object or object look as if it is true and original when in fact it is fake. Falsification of a Driving License (SIM) is a criminal offense against falsifying an authentic letter as stated in article 263 of the Criminal Code and confirmed in article 264 paragraph (1) number 1 of the Criminal Code. The falsification of a SIM card is very common in the city of Pekanbaru, the perpetrators of the falsification of the SIM are the makers of fake SIMs and also users of fake SIMs, with the aim of using SIM facilities that look as if they are true when in fact they contain falsified and non-genuine elements. Fake SIMs circulating within the community are systematic and open, even the perpetrators of fake SIM makers are so easy to offer SIMs from homes to communities in the city of Pekanbaru. The number of criminal cases of forgery of SIMs that occur in the community is still a broad problem, fake SIMs that circulate openly have a bad impact on order on the highway. Efforts from law enforcement against counterfeit SIMs have not been minimized properly, law enforcement is still actively carried out on countermeasures only.This research is a sociological legal research that is research that wants to see the unity between law and society with the gap between Das Sollen and Das Sein. This research was conducted in the Pekanbaru City Police jurisdiction, while the population and sample were all parties related to the problem examined in this study, the data sources used, Primary data, secondary data, and tertiary data. Data collection techniques in this study were carried out through interviews, questionnaires, and literature review.From the results of this study, the law enforcement efforts are illustrated. First, law enforcement efforts Preventive and Refressive have been carried out by law enforcers, while in reality the field that preventive law enforcement is still not optimal. Second, there are obstacles that hinder the implementation of Preventive law enforcement, such constraints as lack of integrity and professional law enforcement, people who are less concerned, are legally blind and do not understand the procedures for making official and correct SIMs, conditions of police facilities and pre-facilities are still lacking, and perpetrators of crimes that intelligent and systematic fraud. Thirdly, efforts are made to reduce barriers to law enforcement in minimizing criminal acts of forgery of SIM by conducting moral and character strengthening of law enforcers, forming a fake SIM Eradication Task Force Task Force, and improving the facilities and pre-facilities of police to support the improvement of law enforcement against falsification of SIM in the city of Pekanbaru.Keywords: Law Enforcement - Criminal Acts - Falsification of SIM